2006
DOI: 10.1163/157181806778458121
|View full text |Cite
|
Sign up to set email alerts
|

Freedom and Autonomy of Street Children

Abstract: Brill reduces number of Supervisory Board members to three Today, Brill's Combined Meeting resolved to reduce the number of Supervisory Board members from four to three. The Board has elected unanimously Mr. Robin Hoytema van Konijnenburg, to be appointed as chairman and Mr. Theo van der Raadt as vice-chairman. These changes are effective immediately after the upcoming Annual General Meeting of Shareholders of 25 June, 2020 (starting at 2.00 PM). As a result, the agenda items number 6a: 'Giving opportunity for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 15 publications
3
16
0
Order By: Relevance
“…The tunnel vision found during the qualitative study is similar to the findings of Schimmel (), who perceived adaptive preferences in street children. Adaptive preferences are social unjust choices that make individuals normalize or endure a social unjust situation (Sen, ).…”
Section: Resultssupporting
confidence: 86%
“…The tunnel vision found during the qualitative study is similar to the findings of Schimmel (), who perceived adaptive preferences in street children. Adaptive preferences are social unjust choices that make individuals normalize or endure a social unjust situation (Sen, ).…”
Section: Resultssupporting
confidence: 86%
“…This is a critical area that requires further in-depth investigation. The information obtained, disconcerting as it was, demonstrates and confirms the resilience of these children as illustrated by several authors (Boyden & Mann, 2005;Henry, 2001;Schimmel, 2006) and inspired an extensive literature review on the concept "street children".…”
Section: Introductionsupporting
confidence: 63%
“…Findings from Schimmel (2006) and Association for Development, Delhi (2002) showed that condition of the street children after migration to the streets are vulnerable and they are facing multi dimensional problems. But the current study illustrates that children living with the family are indigent families, who migrated from different areas some of them stay in the recognized slums of Kolkata.…”
Section: Discussionmentioning
confidence: 99%